Assessing the validity of random blood glucose testing for monitoring glycemic control and predicting HbA1c values in type 2 diabetics at Karl Bremer Hospital - Oyekemi Funke, Daramola (Stellenbosch : University of Stellenbosch, 2015)
Thesis (MFamMed)--Stellenbosch University, 2012